2020
DOI: 10.1002/fam.2879
|View full text |Cite
|
Sign up to set email alerts
|

New copper(II)‐coordinated epoxy‐amine polymers with flame‐self‐extinguishment properties: Elaboration, combustibility testing, and flame propagation rate measuring

Abstract: Summary In the DGEBA ‐ pepa ‐ CuSiF6 system (DGEBA is diglycidyl ether of bisphenol A; pepa is polyethylenepolyamine containing ethylenediamine (eda) and diethylenetriamine (deta)), a new flame retardant‐hardener for epoxy resins in the form of a chelate complex [Cu(eda)(deta)]SiF6 was synthesized and incorporated into the DGEBA to obtain a number of CuSiF6‐containing epoxy‐amine polymers with reduced combustibility and flame‐self‐extinguishment properties. The resulting samples of the DGEBA/pepa‐CuSiF6(I‐V) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…The flame-retardant coating based on epoxy-amine polymers modified with copper(II) hexafluorosilicate can be obtained in two ways. According to the first method, the polymer sample is obtained starting from the flame retardant-hardener and the binder [29]. For this, the [Cu(eda) (deta)]SiF 6 chelate complex is mixed with ED-20.…”
Section: Synthesis Of a Flame Retardant-hardener For Epoxy Resins And Preparation Of A Flame-retardant Coating For Woodmentioning
confidence: 99%
See 1 more Smart Citation
“…The flame-retardant coating based on epoxy-amine polymers modified with copper(II) hexafluorosilicate can be obtained in two ways. According to the first method, the polymer sample is obtained starting from the flame retardant-hardener and the binder [29]. For this, the [Cu(eda) (deta)]SiF 6 chelate complex is mixed with ED-20.…”
Section: Synthesis Of a Flame Retardant-hardener For Epoxy Resins And Preparation Of A Flame-retardant Coating For Woodmentioning
confidence: 99%
“…Due to their unusual ability to form chelate complexes, these copper(II) salts can be incorporated into the polymer framework of the composites, which ensures that the performance characteristics of these epoxy-amine composite materials are supported at the proper level [25,26]. These results prompted the search for new fire retardants for epoxy resins [27,28] to obtain epoxy-amine composite materials with a reduced fire hazard [29], which could be used as a fire-retardant coating for wood.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, chelate complexes [1] of many d-metals with polyamines [2] due to their thermal stabilization [3][4][5][6][7][8] caused by the chelating effect are widely used as flame retardants and hardeners of epoxy resins [9][10][11][12][13][14][15]. Among the great number of polydentate ligands, ethylenediamine (en) is known to use as an efficient curing agent to produce epoxy-polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…The results of experimental studies have shown that the addition of even a small amount of an inorganic copper(II) salt to epoxy–amine polymers (EAPs) provides a significant reduction in the combustibility of epoxy‐based polymer materials 28,29 . In particular, the controlled addition of copper(II) hexafluorosilicate (flame retardant) to ordinary epoxy–amine composites increases their ignition and self‐ignition temperatures by an average of 15°C‐34°C and 25°C‐58°C, respectively.…”
Section: Introductionmentioning
confidence: 99%